The Relationship of Islamic Spirituality, Self-Compassion, and Husband Support with Subjective Well-Being in the Late Trimester of Pregnant Women during the COVID-19 Pandemic - Khairiyah, Nadiah Al; Anganthi, Nisa Rachmah Nur (Universitas Muhammadiyah Surakarta, 2022)
The health of pregnant women in the late trimester preparing for childbirth is vulnerable to being affected by the conditions around them. The state of the COVID-19 pandemic adds to the risk factors for pregnant women. The perceived impact is stress, anxiety to depression which can interfere with the health and safety of the mother and fetus. The importance of pregnant women in maintaining their mental health can be seen from the condition of subjective well-being. A pregnant woman’s subjective well-being can be influenced by internal factors such as Islamic spirituality and self-compassion. In addition, external factors also affect, such as the husband's support. This study examined the relationship between Islamic spirituality, self-compassion, and husband's support with subjective well-being in late-trimester pregnant women during the COVID-19 pandemic. This study used a quantitative correlational method, with the number of participants being 103 pregnant women. The data collection technique used was convenience sampling and had criteria as Indonesian citizens, Muslim women aged 20-45 years who experienced late trimester pregnancy during the COVID-19 pandemic (November 2021-January 2022). The data obtained were then analyzed using a multiple linear regression test. Based on the results of this study, it found that Islamic spirituality, self-compassion, and husband's support had a relationship with subjective wellbeing worth R=0.606, with an effective contribution of 36.7%. The results of this study show new findings that most of the late trimester pregnant women during this pandemic have moderate Subjective Well-being.